If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 91 = x + 97 Reorder the terms: 91 + x = x + 97 Reorder the terms: 91 + x = 97 + x Add '-1x' to each side of the equation. 91 + x + -1x = 97 + x + -1x Combine like terms: x + -1x = 0 91 + 0 = 97 + x + -1x 91 = 97 + x + -1x Combine like terms: x + -1x = 0 91 = 97 + 0 91 = 97 Solving 91 = 97 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 11e=9e+4 | | 5+2x=9.50 | | 4d^2+64=0 | | 2x-3x=14 | | -3n+11-7n=-13 | | 2z-1=z+8-22 | | x+91=x+971 | | x^2-22xy-48y^2= | | x/4-10=-13 | | -3+11-7n=-13 | | 6c-12+4c=8c | | -3+9=a | | 81-(6*9)=1 | | 19f^2-17k-2=0 | | 3s-4+6s+7= | | 18x^2+9x-20=0 | | d^2-14d+13=0 | | -6/5=a | | 16x-5=105 | | -5(4r+8)=16-3r | | (7x+2)(3x^3-14x-5)=0 | | 7x=434 | | 12+1234567890=x(43+83) | | -5-3x=-4x-8 | | 3m^2-13m+12=0 | | 312+2y=36 | | 13=-2-5x | | 16=2x-2 | | -3(2+5y)=-26 | | 4(b-2)=2(2c+2) | | 2x-6=12+11x | | -.5=6-.66x |